Effect of a-InGaZnO TFT Channel Thickness under Self-Heating Stress. (1st January 2019) - Tai, Mao-Chou; Chang, Po-Wen; Chang, Ting-Chang; Tsao, Yu-Ching; Tsai, Yu-Lin; Tu, Hong-Yi; Wang, Yu-Xuan; Chen, Jian-Jie; Lin, Chih-Chih
Abstract : In this work, indium-gallium-zinc-oxide thin film transistors (IGZO-TFTs) with different channel thicknesses were compared after self-heating stress (SHS). Although TFTs with a thicker channel have higher current during stress conditions, less degradation is reported. This degradation, manifest as the threshold voltage shift in the transfer characteristics, is well described by the stretched-exponential equation. In addition, the average effective barrier height, Eτ, is extracted to compare the difference in degradation between both TFTs, and finds that the barrier height in the thick channel device is twice that of the thin channel device. Finally, a COMSOL simulation is performed to demonstrate the electrical difference at the gate insulator layer and confirm such phenomena.